(untitled) (Central Asian Journal of Medical Sciences, 2022)
Objective: In the following clinical case we focused on the differential diagnosis in case of fever and neurological symptoms after a trip to the tropics. Methods: The diagnosis was made through clinical and laboratory tests. Results: A healthy 25-year-old woman comes to her family doctor with a fever that appeared 3 days after returning from a trip to Brazil that sends her to hospital for suspected meningitis. Serologies reveal a positivity for Dengue (Dengue IgG rapid test negativ, Dengue IgM rapid test positiv, Dengue rapid test NS1 Antigen positiv). Conclusion: Treatment of Dengue is in most cases symptomatic. Cases of severe dengue are rare. The vaccine is recommended for people aged 9 to 45 who have already been infected with dengue in the past and who live in areas where Dengue is endemic.